Hemorrhagic risk after intravenous thrombolysis for ischemic stroke in patients with cerebral microbleeds and white matter disease - Capuana, Maria Luisa (Neurol Sci, 2020)
OBJECTIVES: Aim of this study was to evaluate the association between cerebral microbleeds (CMBs) and white matter disease (WMD) with intracerebral hemorrhage (ICH) after intravenous thrombolysis (IVT) with rt-PA. We also evaluated whether CMBs characteristics and WMD burden correlate with symptomatic ICH and outcome. METHODS: We included acute ischemic stroke (AIS) patients treated with IVT. The number and location of CMBs as well as severity of WMD were rated analyzing pre- or post-treatment MRI. Multivariable regression analysis was used to determine the impact of CMB and WMD on ICH subgroups and outcome measures. RESULTS: 434 patients were included. CMBs were detected in 23.3% of them. ICH occurred in 34.7% of patients with CMBs. Independent predictors of parenchymal hemorrhage were the presence of CMBs (OR 2.724, 95% CI 1.360–5.464, p = 0.005) as well as cortical-subcortical stroke (OR 3.629, 95% CI 1.841–7.151, p < 0.001) and atherothrombotic stroke subtype (OR 3.381, 95% CI 1.335–8.566, p = 0.010). Either the presence, or number, and location of CMBs, as well as WMD, was not independently associated with the development of SICH. No independent association between the presence, number, or location of CMBs or WMD and outcome measures was observed. CONCLUSIONS: The results of our study suggest that the exclusion of eligible candidates to administration of IV rt-PA only on the basis of CMBs presence is not justified. The clinical decision should be weighed with a case-by-case approach. Additional data are needed to evaluate the benefit-risk profile of rt-PA in patients carrying numerous microbleeds. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10072-020-04720-y) contains supplementary material, which is available to authorized users.